ANALYSIS OF MANAGEMENT STRATEGIES FOR EDUCATIONAL IMPROVEMENT (STUDY ON PRIVATE SCHOOLS IN THAILAND) - Darmayanti, Novi; Nashrullah, Muhammad Hafidh; Wahyuningtyas, Eka; Aisyah, Nur; Melati, Puput; Waedaramae, Waefatimoh (Journal of Social Comunity Services, 2024)
General Background: The efficacy of management strategies in enhancing educational outcomes has become increasingly critical, especially in the context of private schools. Specific Background: In Thailand, private schools face unique challenges that necessitate innovative approaches to curriculum development and educational quality. Knowledge Gap: Existing literature reveals limited empirical studies on the impact of curriculum innovation, technology integration, and business partnerships on private school performance in Thailand. Aims: This research aims to evaluate management strategies that improve performance in Thai private schools, with a specific focus on curriculum development and its role in elevating educational standards. Results: Utilizing a mixed-methods approach, including literature reviews, case studies, and cross-sectional primary data collected through observations and interviews with schools in Southern Thailand, the study identifies that relevant, innovative, and competency-based curricula are pivotal in enhancing educational quality. The integration of technology and establishment of business partnerships are also critical in preparing students for future challenges. Novelty: This study contributes to the existing body of knowledge by providing empirical evidence on the effectiveness of these strategies in the Thai private school sector and by evaluating their impact through direct international community service initiatives. Implications: The findings suggest that sustainable and responsive curriculum development is essential for improving the competitiveness of private schools in Thailand, offering valuable insights for educational policy-makers and school administrators aiming to foster long-term educational improvements.